EVALUATION OF SUSPENDING AND EMULSIFYING PROPERTIES OF CITRULLUS LANATUS SEEDS GUM - Chaudhari, Shilpa Praveen; Akuskar, Ganesh; Salvankar, Shailendra S; Bangar, Jeetendra (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â The biphasic formulations were aimed with firstly to evaluate the Citrullus lanatus seed gum for its rheological properties secondly, compare between the flocculating behavior of C. lanatus and tragacanth, there suspending properties and thirdly comparison between there emulsifying activity. In this context, the gum was evaluated at different pH, temperature, RPM etc., and found that with an increase in pH and decrease in temperature viscosity increases. Then the suspensions of paracetamol were prepared and compared with different concentrations (0.5%, 1%, 1.5% and 2% w/v) of C. lanatus and tragacanth gum. Their sedimentation profile, pH, and rheological behavior were compared and found to show no sedimentation in 7 days study with less viscosity and comparable degree of flocculation to tracaganth. Flocculation study of C. lanatus seed gum reveals that flocculation ability of C. lanatus seed gum was more than gum tracaganth at lower concentration. For comparing the emulsifying activity, castor oil was taken as a model drug and emulsified with C. lanatus gum and gum acacia. C. lanatus gum showed good stability for the emulsion. From the study above it can be concluded that the C. lanatus seed gum acts as very good suspending agent than gum tracaganth and can be used in low concentration as emulsifier compared to acacia gum. Keywords: Citrullus lanatus, Emulsifier, Acacia gum, Pharmaceutical excipients, Emulsion, Suspending agents, Rheology, Flocculation.